Airborne bacteria in the atmosphere: Presence, purpose, and potential. (August 2016) - Smets, Wenke; Moretti, Serena; Denys, Siegfried; Lebeer, Sarah
Abstract: Numerous recent studies have highlighted that the types of bacteria present in the atmosphere often show predictable patterns across space and time. These patterns can be driven by differences in bacterial sources of the atmosphere and a wide range of environmental factors, including UV intensity, precipitation events, and humidity. The abundance of certain bacterial taxa is of interest, not only for their ability to mediate a range of chemical and physical processes in the atmosphere, such as cloud formation and ice nucleation, but also for their implications -both beneficial and detrimental-for human health. Consequently, the widespread importance of airborne bacteria has stimulated the search for their applicability. Improving air quality, modelling the dispersal of airborne bacteria (e.g. pathogens) and biotechnological purposes are already being explored. Nevertheless, many technological challenges still need to be overcome to fully understand the roles of airborne bacteria in our health and global ecosystems. Highlights: Understanding the presence of airborne bacteria in the atmosphere. Unravelling the roles airborne bacteria have on atmospheric processes and health. Exploring the underlying potential of airborne bacteria for various applications.